Кластерный анализ территории Украины по основным показателям повседневного функционирования и проявления техногенной опасности - Тютюник, В.В.; Бондарев, Н.В.; Шевченко, Р.И.; Черногор, Л.Ф.; Калугин, В.Д. (Геоінформатика, 2014)
В рамках предлагаемого энергетического подхода представлены результаты оценки методами кластерного анализа взаимосвязи между основными показателями жизнедеятельности природно-техногенно-социальной системы (ПТС системы) Украины в режиме повседневного функционирования и в условиях проявления чрезвычайных ситуаций техногенного происхождения. Приведены результаты кластеризации регионов Украины по основным переменным, определяющим условия повседневного функционирования ПТС системы и проявления техногенной опасности. У межах запропонованого енергетичного підходу розглянуто результати оцінки методами кластерного аналізу взаємозв’язків між основними показниками життєдіяльності природно-техногенно-соціальної системи (ПТС системи) України в режимі повсякденного функціонування та в умовах прояву надзвичайних ситуацій техногенного походження. Наведено результати кластеризації регіонів України за основними змінними, які визначають умови повсякденного функціонування ПТС системи та прояву техногенної небезпеки. Purpose. The purpose of the paper is to develop, within the suggested power approach, conceptions of dynamics and power functioning of the natural-technogenic-social system with dispersed in time and space any sources of dangers and their destabilizing effect on safety by daily functioning; to classify and range the territory of Ukraine by levels of daily functioning and technogenic danger manifestation.
Design/methodology/approach. We used methods of cluster analysis to carry out research on classification and ranging of the territory of Ukraine by levels of danger of a technogenic origin based to an assessment of the main indicators of the country`s activity and various manifestations of technogenic dangers – emergency situations of a technogenic origin; on fires in technogenic and social environment; on road accidents. The data analysis was carried out using statistical STATISTICA 6.1 and SPSS 20 packages.
Findings. On the basis of a hierarchical clustering, we carried out: a) ranging by quantity of interrelations between indicators of the activity of the natural-technogenic-social system of Ukraine in a mode of daily functioning and in the conditions of emergency situations of a technogenic origin; b) ranging of regions of Ukraine by key parameters defining conditions of daily functioning of the natural – technogenic – social system and manifestation of technogenic danger. On the basis of non-hierarchical clustering by the method of k-averages we carried out an assessment of the degree of clustering of the main variables defining conditions of daily functioning of the natural – technogenic and social system and manifestation of technogenic danger.
Practical value/implications. The obtained results of hierarchical and non-hierarchical clustering offer scientific foundation for further development of an effective territorial complex system of monitoring, prevention and elimination of emergency situations of a technogenic origin and ensuring ecological safety in Ukraine.